2015
DOI: 10.1111/jgs.13230
|View full text |Cite
|
Sign up to set email alerts
|

Rationales that Providers and Family Members Cited for the Use of Antipsychotic Medications in Nursing Home Residents with Dementia

Abstract: The rationale for use of antipsychotic drug therapy frequently relates to a wide variety of indications for which these drugs are not approved and for which evidence of efficacy is lacking. These findings have implications for clinical practice and policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 11 publications
(18 reference statements)
0
44
0
Order By: Relevance
“…Antipsychotics are commonly prescribed to older adults with dementia in community and long‐term care (LTC) settings for neuropsychiatric symptoms . However, they are considered inappropriate for many of the specific behaviors of concern .…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotics are commonly prescribed to older adults with dementia in community and long‐term care (LTC) settings for neuropsychiatric symptoms . However, they are considered inappropriate for many of the specific behaviors of concern .…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic (AP) prescribing has frequently been recognized as a last-resort solution in order to manage disturbing symptoms such as aggression and agitation, and psychotic symptoms such as delirium and hallucinations [3]. There is a general lack of evidence about AP efficacy in older people with dementia and about risks of serious adverse events, including short and long-term increased mortality rates [46].…”
Section: Introductionmentioning
confidence: 99%
“…loss of contact with reality, depression, anxiety) and behavioural reasons (e.g. verbal and physical aggression), emotional reasons were cited for the use of antipsychotics including that the resident was angry or agitated, or even ‘sad’ or ‘crying’ – thus also linking emotional consequences to inappropriate prescribing …”
Section: Discussionmentioning
confidence: 99%
“…A recent US study found that the reasons given for the use of antipsychotic medication in nursing-home residents with dementia frequently related to a wide variety of indications for which the medications are not approved and for which evidence of efficacy is lacking. [19] For example, as well as psychiatric (e.g. loss of contact with reality, depression, anxiety) and behavioural reasons (e.g.…”
Section: Discussionmentioning
confidence: 99%